2014
DOI: 10.1016/j.bjorl.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

New clinical staging for pharyngeal surgery in obstructive sleep apnea patients

Abstract: The presence of hypertrophic palatine tonsils was the anatomical factor in common in the most successful stages (I, II, and V), regardless of body mass index. Although the modified Mallampati index classes 3 and 4 reduced the success rate of surgery in patients with hypertrophic tonsils (stage II), the presence of modified Mallampati index classes 1 and 2 did not favor surgical success in patients with normal tonsils (stage III).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…A PT grading scale has been used to predict OSA severity and the efficacy of tonsillectomy in treating OSA. A higher grade, which corresponds with larger and more exophytic tonsils, corresponds with higher preoperative AHI values and a more significant reduction in AHI after removal 1669,1671 . A small series noted improvement in AHI in selected patients with small tonsils after tonsillectomy 1672 .…”
Section: Surgical Treatment For Osamentioning
confidence: 97%
See 1 more Smart Citation
“…A PT grading scale has been used to predict OSA severity and the efficacy of tonsillectomy in treating OSA. A higher grade, which corresponds with larger and more exophytic tonsils, corresponds with higher preoperative AHI values and a more significant reduction in AHI after removal 1669,1671 . A small series noted improvement in AHI in selected patients with small tonsils after tonsillectomy 1672 .…”
Section: Surgical Treatment For Osamentioning
confidence: 97%
“…A higher grade, which corresponds with larger and more exophytic tonsils, corresponds with higher preoperative AHI values and a more significant reduction in AHI after removal. 1669,1671 A small series noted improve-ment in AHI in selected patients with small tonsils after tonsillectomy. 1672 Jara and Weaver 327 found a strong correlation between the subjective and objective tonsil measures that were consistent with the findings of previous studies, and they suggested that PT grade, rather than volume, may be more predictive of the severity of OSA.…”
Section: Ixd3 Tonsillectomymentioning
confidence: 99%
“…Pharyngeal surgery consisted of tonsillectomy, hemostasis with bipolar electrocautery and 2-0 catgut sutures, closure of muscle and mucosal tissues with interrupted 3-0 Vicryl sutures, detachment of the palatal webbing, and resection of excess uvular mucosa when necessary. The surgical technique has been described in detail by Vidigal et al 15 Nasal surgery (turbinectomy with or without septoplasty) was performed simultaneously with pharyngeal surgery. No nasal packing was used.…”
Section: Methodsmentioning
confidence: 99%
“…and more exophytic tonsils, corresponds with higher preoperative AHI values and a more significant reduction in AHI after removal 1668,1670 . A small series noted improvement in AHI in selected patients with small tonsils after tonsillectomy.…”
Section: Accepted Articlementioning
confidence: 95%